2017
DOI: 10.1590/s1679-45082017ao3945
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cigarette smoking on ventricular repolarization in adolescents

Abstract: Objective To assess the association between cigarette smoking and ventricular arrhythmias in adolescents. Novel electrocardiographic parameters –Tp-e interval, as well as Tpe/QT and Tpe/QTc ratios – were used to make this assessment.Methods The study population consisted of 87 subjects aged between 16-19 years. Fifty-one adolescent smokers with no risk of arrhythmia comprised the Smoker Group, and 36 adolescents who had never smoked cigarettes comprised the Control Group. Smokers were defined as patients smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Our results are in consistence with the results of the studies evaluating the effect of smoking (36) and subclinical hypothyroidism (37) on ventricular repolarization indexes. Similar to our study, these studies have shown that without a concomitant QTc prolongation Tp-e interval and Tp-e/QTc ratio may increase.…”
Section: Discussionsupporting
confidence: 89%
“…Our results are in consistence with the results of the studies evaluating the effect of smoking (36) and subclinical hypothyroidism (37) on ventricular repolarization indexes. Similar to our study, these studies have shown that without a concomitant QTc prolongation Tp-e interval and Tp-e/QTc ratio may increase.…”
Section: Discussionsupporting
confidence: 89%
“…49 Nicotine that is released into the circulation during smoking is clearly known to increase the plasma catecholamines, thus affecting the heart rate, and arterial BP and as a result of all those alterations augmented myocardial work and oxygen demand may contribute to the generation of cardiac arrhythmias. 50 However, additional research is necessary to determine the relationship between smoking and palpitations as the causes may be multifactorial. Furthermore, smokers had a statistically significant higher SBP level than non-smokers besides no significant difference in DBP level between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, prolonged QTc interval may be associated with cigarette smoking [ 53 ] and alcohol consumption [ 54 ]. Several studies demonstrated that smoking is a major cause of atherosclerosis-related cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%